Optimization of Power Systems for Low-Carbon Manufacturing in New Energy Vehicles - Li, Dongqing (Simen Owen Academic Proceedings Series, 2026)
The transition toward carbon neutrality has intensified the need for low-carbon manufacturing in the new energy vehicle (NEV) industry. While existing research has primarily focused on the use phase of vehicles, limited attention has been given to the carbon emissions and energy consumption arising during the development and manufacturing of power systems. To address this gap, this study establishes an integrated Energy-Carbon-Cost (ECC) framework that combines lifecycle assessment (LCA), empirical industrial data, and multi-objective optimization modeling. The framework quantifies how design parameters, such as material substitution, motor efficiency, and cooling configurations, affect lifecycle carbon intensity, cost, and energy efficiency. Results based on case studies from SAIC, BYD, and Volkswagen demonstrate that optimized configurations can reduce total lifecycle carbon emissions by approximately 24% while maintaining economic feasibility. The proposed model transforms traditional LCA from a static evaluation tool into a dynamic, prescriptive decision system, enabling both theoretical innovation and practical applicability. This research provides manufacturers and policymakers with an actionable pathway for achieving synergistic carbon reduction and cost optimization, contributing to the sustainable advancement of NEV manufacturing.